Treatment of Active Acne Vulgaris by Chemical Peeling Using 88% Lactic Acid - Khalifa E. Sharquie; Adil A. Noaimi; Entesar A. Al-Janabi (Our Dermatology Online, 2014)
Introduction: The etiopathogenesis of acne vulgaris is multifactorial, and its therapy is prolonged course that might be not accepted by many patients. Most recently TCA 35% one session peeling gave complete clearance and full remission for active acne vulgaris. Lactic acid has been used effectively as therapeutic topical agents for many skin diseases. Aim: To evaluate the efficacy and safety of chemical peeling using 88% lactic acid solution in the treatment of active acne vulgaris. Material and Methods: This clinical, interventional, therapeutic study was done at the Department of Dermatology, Baghdad Teaching Hospital, during the period from October 2012 to October 2013. Twenty five patients with active acne vulgaris were included, 15 (60%) females and 10 (40%) males and their ages ranged from 16-36 (21.5000± 5.46279) years. Fifteen patients were associated with acne scars. Three chemical peels using 88% lactic acid solution was carried out two weeks apart for patients with active acne vulgaris with or without scarring. Scoring for active acne vulgaris and acne scar was done for each case before and after operation to evaluate the severity of acne and the degree of scar before and after treatment. All patients were with Fitzpatrick's skin types III and IV. Patients were followed up every two weeks during period of therapy and monthly for 3 months after stopping the treatment. Results: Twenty five patients with active acne vulgaris were treated with 3 sessions of lactic acid, fifteen patients had associated acne scar. Scoring for active acne vulgaris including papules and pustules showed highly statistically significant reduction after 2 weeks of therapy (p=0.0001), after 4 weeks (p=0.0001)and after 6 weeks (p=0.0001), with percent reduction 87.2% for papules and 94% for pustules after end of sessions while after 3 months follow up the reduction rate for papules 93.8% and p-value (p=0.001) and for pustules 97.6% and (p=0.0001). While the scarring reduction was moderate in 3 (20%) patients, marked in 3 (20%) patients and excellent in 9 (60%) patients with statistically significant reduction (p=0.002). All patients had full satisfaction about the results of peeling. Post inflammatory hyperpigmentation was observed few weeks after peeling but follow up for 3 months showed complete clearance of pigmentation with lightening and tightening of skin. Conclusions: Chemical peeling using 88% lactic acid is an effective mode of therapy for active acne vulgaris and acne scar in patient with dark complexion..